A comparison of UK domestic water services sizing methods with each other and with empirical data. (November 2017) - Tindall, Jess; Pendle, Jamie
Evidence suggests that domestic cold water service sizing methods in many countries around the world tend to overestimate the actual peak water volume flow rate. Oversizing domestic water service systems does waste materials and money, but it also increases the length of time that it takes for water to pass through the system which can increase water temperatures with the associated risks that presents. This paper compares the three commonly used UK domestic cold water service sizing methods and reveals variance in the methods, the design flow rates calculated and the amount of diversity applied by each method. BS EN 806 returns the lowest design flow rates of the three methods and also applies significantly greater diversity. Empirical domestic cold water service volume flow rate data from two case study buildings revealed that all three UK sizing methods significantly overestimated the peak water volume flow rates but that BS EN 806 was the closest. Additional empirical data from seven more buildings have been used to validate the data from this study and add confidence to the findings. This research provides useful evidence to help engineers select the most appropriate UK domestic cold water service sizing method and to anticipate the likely range and fluctuation of domestic cold water service flow rates. Practical application : Engineers tend to be conservative by nature and generally err on the side of caution to ensure that there is never any cause for customer complaint about their designs. This is understandable but there can be negative consequences if the full implications of such decisions are not fully understood. This paper reveals significant oversizing compared to empirical data from each of the three UK domestic water service sizing methods and highlights the reasons for this. The practical application of this paper lies in the presented results data and analysis which will help engineers make this important choice between the available sizing methods.